(4+12i)(6-12i)=0

Simple and best practice solution for (4+12i)(6-12i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4+12i)(6-12i)=0 equation:



(4+12i)(6-12i)=0
We add all the numbers together, and all the variables
(12i+4)(-12i+6)=0
We multiply parentheses ..
(-144i^2+72i-48i+24)=0
We get rid of parentheses
-144i^2+72i-48i+24=0
We add all the numbers together, and all the variables
-144i^2+24i+24=0
a = -144; b = 24; c = +24;
Δ = b2-4ac
Δ = 242-4·(-144)·24
Δ = 14400
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$i_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$i_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{14400}=120$
$i_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(24)-120}{2*-144}=\frac{-144}{-288} =1/2 $
$i_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(24)+120}{2*-144}=\frac{96}{-288} =-1/3 $

See similar equations:

| -20+w=-4 | | 10y=35=3y | | 10x+4=-3 | | -18x+24=24-18x | | 1.85=a(5.39-9.04)^2+2.2 | | 1.85=a(5.39-9.04)+2.2 | | 75°+40°=65+x | | 5(x+3)+3=-12 | | 2(x+4)-4x+9=5-(2x+6) | | 3/5(x-10=18-4x-1 | | 2x²+12x-18=0 | | 4-6x-2=-6x-2 | | *x2/3=360 | | 77x-x=304 | | 7.66=-22.73+m | | (s+6)+(s+6)+2s+s+s=102 | | (5x+4)°=89° | | y/1.2=24 | | y-7=200 | | w+3.8=7.28 | | 66x+3x=345 | | 7(x+2)+4=7x+5 | | 6z=13 | | 4(u-3)-9=-5(-4u+7)-8u | | 6c-13=47 | | 3w-3=-3(w-7) | | 3.8x=57 | | 18=3(u+2)-5u | | 314+x=700 | | -9(w-1)=-4w+49 | | 3(w-2)-7w=26 | | -8+2y=-6-2 |

Equations solver categories